Evidence that no liquid equilibrium process is involved in the comb building of honey bees (Apis Mellifera) - Oeder, Robert; Schwabe, Dietrich; Justus Liebig University Giessen (My University, 2017)
According to Pirk et al. (2004), honeybees first build free standing cylindrical cells which are then transformed to hexagonal cross-section by wax-flow in a kind of self-organization. We show that there is no self-organization of the wax. Bees cannot form juxtaposed wax tubes which are in contact to each other. They would have to produce temperatures close to the melting point in order to accomplish flow of the wax in a time which is meaningfully short for honeycomb construction. The cells would collapse at this temperature. The form of the comb-cells adjacent to the walls of the nest cannot stem from circular tubes. From this it is clear that bees build their honeycomb in a direct and holistic way. They begin and continue building at the edge of the mid-wall. The combination of the following two principles inevitably generates the hexagonal cross-section of the cells: (1) the hexagonal close packing of the cells and (2) a common wall between all adjacent cells. This results in an economic use of space and material. The mid-wall can be considered as assembled of parts of Plateau s minimum plane of the regular tetrahedron and is built with minimum consumption of wax as are the cells.

Nach Pirk et al. (2004) bauen Honigbienen beim Wabenbau zunächst frei stehende zylindrische Zellen, die dann durch das Fließen des Wachses in einer Art Selbstorganisation in den hexagonalen Querschnitt umgeformt werden. Wir zeigen, dass Selbstorganisation des Wachses nicht auftritt. Bienen können keine dicht nebeneinander liegenden, sich berührenden Wachsröhren bauen. Um ein Fließen des Wachses in einer für den Wabenbau sinnvoll kurzen Zeit zu bewerkstelligen, müssten sie Temperaturen knapp unterhalb des Schmelzpunktes erzeugen. Bei dieser Temperatur würden die Zellen kollabieren. Die Form der Zellen im Kontakt mit den Wänden der Nisthöhle kann nicht aus runden Röhren entstanden sein. Das macht klar, dass Bienen ihre Waben direkt und in einer ganzheitlichen Weise bauen. Sie beginnen den Bau mit der Mittelwand und bauen an deren Rand sukzessive weiter. Die Kombination folgender zwei Prinzipien erzeugt zwangsläufig den hexagonalen Querschnitt der Zellen: (1) die hexagonal dichteste Packung der Zellen und (2) eine gemeinsame Wand zwischen allen benachbarten Zellen. Das führt zu einer ökonomischen Nutzung von Raum und Material. Die Mittelwand kann als aus Teilen der Plateau schen Minimalfläche des regulären Tetraeders zusammengesetzt betrachtet werden.
Keywords: comb building; hexagonal cells; mid-wall; minimum consumption of wax; ddc:500